1984
DOI: 10.2307/2443335
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopy of the Resin Glands of Passiflora foetida (Passifloraceae)

Abstract: Petiolar, bracteolar, and stipular glands from two varieties of Passiflora foetida were studied by both light and electron microscopy. These glands have previously been called nectaries. They do resemble the sugar‐secreting glands of other Passiflora species with respect to their location and morphology. However, cytological studies together with chemical tests of the exudate support the view that the glands in the varieties studied actually secrete a resin‐like substance which possibly functions as an anti‐he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Passiflora foetida is a weedy lowland plant for which Baker et al (1978) published extrafloral nectary chemistry from Costa Rican material. Durkee et al (1984) confirmed that the Hawaiian plants lack EFNs, A possible alternative to explain the EFNs observed on Hawaiian plants is that mutualism was established with taxa other than ants. Alternate mutualisms at EFNs have been suggested with parasitic solitary wasps (Koptur 1982, Hespenheide unpubl.…”
Section: Patterns Of Extrafloral Nectaries In the Flora: Hvnpmentioning
confidence: 63%
See 1 more Smart Citation
“…Passiflora foetida is a weedy lowland plant for which Baker et al (1978) published extrafloral nectary chemistry from Costa Rican material. Durkee et al (1984) confirmed that the Hawaiian plants lack EFNs, A possible alternative to explain the EFNs observed on Hawaiian plants is that mutualism was established with taxa other than ants. Alternate mutualisms at EFNs have been suggested with parasitic solitary wasps (Koptur 1982, Hespenheide unpubl.…”
Section: Patterns Of Extrafloral Nectaries In the Flora: Hvnpmentioning
confidence: 63%
“…In addition, they were not visited by nectar feeders in the field. Durkee et al (1984) has confirmed anatomically that plants of Passiflora foetida from Hawaii lack extrafloral nectaries.…”
Section: Methodsmentioning
confidence: 73%
“…Subramanian et al (1990) studying Hiptage sericea and Castro et al (2001) analyzing G. brasiliensis both reached the same conclusion and considered that these structures are homologous. In the same way, Durkee et al (1984) suggested that the EFNs of Passiflora foetida represent a transition to lipid-secreting glands. In additional, Davis et al (2014) consider the conserved floral morphology in Malpighiaceae as a result of extrinsic factor, in especially the plant-pollinator mutualism.…”
Section: Discussionmentioning
confidence: 91%
“…However, these authors opted to call such glands extrafloral nectaries (EFN) based on ultrastructural analyses and detection of sugar in the secretion. Anatomically comparable secretory structures have been described for Hymenaea stigonocarpa (Paiva & Machado 2006), Passiflora foetida (Durkee et al 1984) and Prockia crucis (Thadeo et al 2008), which produce different compounds. In such cases it is necessary to clarify the nature of the secretion.…”
Section: Discussionmentioning
confidence: 92%
“…Necrosis starts at the tip of the colleter by wall thickening and degeneration of cytoplasm, which proceeds basipetally in the colleter tissue. Deeply stained globular bodies appear both in the epithelial and central cells of Allamanda, Mitragyna and Roupelia as Curtis and Lersten (1980) and Durkee et al (1984) observed in the resin glands of Salix and Passiflora, respectively. The cell lumen of the central cell is highly reduced due to increased lignification.…”
Section: Necrosismentioning
confidence: 98%